Colistin: How should It Be Dosed for the Critically Ill? - Landersdorfer, Cornelia B.; Nation, Roger L. (Seminars in Respiratory and Critical Care Medicine, 2015)
Colistin, an “old” polymyxin antibiotic, is increasingly being used as last-line treatment against infections caused by multidrug-resistant gram-negative bacteria. It is administered in patients, parenterally or by inhalation, as its inactive prodrug colistin methanesulfonate (CMS). Scientifically based recommendations on how to optimally dose colistin in critically ill patients have become available over the last decade and are extremely important as colistin has a narrow therapeutic window. A dosing algorithm has been developed to achieve desired plasma colistin concentrations in critically ill patients. This includes the necessary dose adjustments for patients with impaired kidney function and those on renal replacement therapy. Due to the slow conversion of CMS to colistin, a loading dose is needed to generate effective concentrations within a reasonable time period. Therapeutic drug monitoring is warranted, where available; because of the observed high interpatient variability in plasma colistin concentrations. Combination therapy should be considered when the infecting pathogen has a colistin minimum inhibitory concentration above 1 mg/L, as increasing the dose may not be feasible due to the risk for nephrotoxicity. Inhalation of CMS achieves considerably higher colistin concentrations in lung fluids than is possible with intravenous administration, with negligible plasma exposure. Similarly, for central nervous system infections, dosing CMS directly into the cerebrospinal fluid generates significantly higher colistin concentrations at the infection site compared with what can be achieved with systemic administration. While questions remain to be addressed via ongoing research, this article reviews the significant advances that have been made toward optimizing the clinical use of colistin.
Keywords: colistin; critically ill; polymyxins; colistin methanesulfonate; pharmacokinetics; pharmacodynamics; toxicodynamics; optimized dosing